Changes in the information uses and gratifications of virtual communications for Kansas State Research and Extension agents during the COVID-19 pandemic - Katie E Messerla; Katherine J. Starzec; Brandie Disberger; Elaine Johannes (Journal of Applied Communications, 2023)
Kansas State Research and Extension (KSRE) staff have experienced many changes due to the COVID-19 pandemic such as remote work requirements and technology adaptations. The purpose of this study was to determine changes in the use of virtual communications used by K-State Research and Extension agents’ internal communications as a result of the COVID-19 pandemic. This study was guided by uses and gratifications theory to understand Extension agents’ intensity of use of virtual communications channels for internal communications and the effectiveness of virtual communication channels for workplace communication needs. Through a quantitative Qualtrics survey (n = 99) with a series of side-by-side before and after matrix questions, agents indicated how their intensity of virtual communication use has changed; how their use of virtual communications for work tasks has changed, and how effectively virtual communications satisfied gratifications before the pandemic (March 2020) and two years into the pandemic (July 2022). Our results show before the COVID-19 pandemic, texting was the main channel of virtual communication used to communicate within the office; two years into the COVID-19 pandemic, Zoom, texting, and Microsoft Teams were the virtual communications channels most used by KSRE agents. In July 2022, KSRE agents used virtual communications with more intensity than before the pandemic to obtain information, schedule meetings, share work progress, and maintain communications even when working in the office. Results suggest KSRE support training on Zoom and Microsoft Teams and continued use of and training for evolving virtual communication for internal work collaboration in and out of the office.
Keywords: Extension communication; Uses and Gratifications Theory; COVID-19; virtual communication; Zoom